Pengaruh Weight Average Cost of Capital dan Return on Equity Terhadap Nilai Perusahaan Pada Perusahaan Sub-Sektor Makanan dan Minuman yang Terdaftar di BEI Periode 2022-2023 - Siska Yulia Defitri (Politeknik Raflesia Press, 2025)
This study aims to analyze the effect of Weighted Average Cost of Capital (WACC) and Return on Equity (ROE) on firm value in food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2023 period. Firm value is measured using the Price to Book Value (PBV) ratio, which reflects investor perceptions of the company's performance and prospects. This study uses a quantitative approach with secondary data obtained from the companies' annual financial reports. The populations of this study are all companies listed on the IDX in the food and beverage sub-sector. The sample was determined using a purposive sampling method based on the completeness of the research variable data, the sample wa obtained as many as 48 companies and analyzed data for 2 years, so that 96 data were processed and analyzed. The data analysis technique used was multiple linear regression, preceded by a classical assumption test. The result of this study indicate that Weight Average Cost of Capital has no significant effect on Firm Value. Likewise, Return on Equity has no significant effect on Firm Value. Based on the simultaneous test results, it is found that Weight Average Cost of Capital and Return on Equity simultaneously have no significant effect on Firm Value.